Removal of N-nitrosodimethylamine precursors by cation exchange resin: The effects of pH and calcium. (November 2018) - Beita-Sandí, Wilson; Selbes, Meric; Kim, Daekyun; Karanfil, Tanju
Abstract: Cation exchange resins have proved to be efficient in removing precursors of N -nitrosodimethylamine (NDMA). NDMA is a probable human carcinogen with a calculated lifetime cancer risk of 10 −6 at 0.7 ng/L in drinking water. This paper investigated the effect of pH and calcium levels on the removal of NDMA precursors using a cation exchange resin. At pH 5 and 7, 30–50% of NDMA precursors, measured by formation potentials (FPs) changes before and after the treatment, were removed by Plus resin. However, increases in NDMA FPs were observed after the treatment at pH 10 indicating that NDMA precursors were released from the resin. NDMA FPs removals in samples containing 15 and 115 mg/L Ca 2+ were 40% and −10% after the ion exchange treatments at pH 7, respectively. It was found that in the presence of high concentration of calcium only one out of four cation exchange resins released NDMA precursors (probably due to manufacturing impurities). Also, the release of NDMA precursors depended on the calcium concentration and the contact time of the resin with the solution containing calcium. Nonetheless, NDMA precursors release from the resin subsided significantly with increasing the number of regeneration cycles of the resin. Highlights: Calcium selectively removed over NDMA precursors with cation exchange resin. Increase in calcium decreased NDMA precursors removal by cation exchange resin. Acidic and neutral pH favors NDMA precursors removal with cation exchange resin. NDMA precursors release occurred at basic pH and high concentrations of calcium. Release of NDMA precursors from cation exchange resin was resin–specific.